The Effect of Business Incubation, Social Capital, and Financial Support on Startup Performance in Indonesia - Judijanto, Loso; Kumalasari, Nety; Mahmuddin, Mahmuddin; Suyono, Windy Permata (West Science Journal Economic and Entrepreneurship, 2025)
This study examines the influence of Business Incubation, Social Capital, and Financial Support on Startup Performance in Indonesia. The research uses a quantitative approach with a sample of 182 startup entrepreneurs in Indonesia, employing a Likert scale (1-5) and SEM-PLS 3 for data analysis. The results reveal that all three variables have a significant positive impact on startup performance. Specifically, Business Incubation (β = 0.337), Financial Support (β = 0.817), and Social Capital (β = 0.574) were found to have substantial effects. These findings underscore the importance of incubator programs, financial access, and strong networks in fostering the success of startups. The study provides practical implications for policymakers and entrepreneurs, emphasizing the need for enhanced support structures, including improved access to funding, networking opportunities, and mentorship.